JosAnton Artze Harzabal: the influence of the environment on poetry (1969-1979) - Oronoz Anchordoqui, Belen (EGAN, 2021)
In the previous issue (see Egan aldizkaria 2019 3/4), I described JosAnton Artze´s environment and poetry when he adopted the pseudonym Harzabal (1969-1979). In this issue, I will investigate how that environment influences his poetry, that is, on the one hand, I will identify the characteristics related to his committed attitude (those that place him in the more universal context of coun- terculture and those that root him in our Basque Cultural Front) and, on the other hand, I will focus on the sperimental characteristics of his poetry (of con- crete poetry).